ChemInform Abstract: Expedient Synthesis of Biologically Important Sulfonylmethyl Pyrimidines. Issue 52 (29th December 2014) - Blades, Kevin; Demeritt, Julie; Fillery, Shaun; Foote, Kevin M.; Greenwood, Ryan; Gregson, Clare; Hassall, Lorraine A.; McGuire, Thomas M.; Pike, Kurt G.; Williams, Emma
Abstract Two novel strategies for the synthesis of sulfonylmethyl pyrimidines are presented.